Kebebasan Berbisnis dan Harga Saham di Lima Negara Asean - Wulandari, Dwi (Universitas Brawijaya, Indonesia, 2013)
The purpose of this research is to understand the impact of economic freedom and monetaryvariables in five ASEAN countries namely Indonesia, Malaysia, Thailand, Philippines and Singapore. Economic freedom of these countries is varied. Singapore can be categorized as free; whereas, Malaysia and Thailand are moderately free. Indonesia and Philippines are mostly unfree.It was found that there were different variables affecting stock price in these countries. In Indonesia, stock price are affected bystock prices in the past. In Malaysia, stock prices are affected by exchange rate. While in Thailand, stock prices are affected by interest rate. In Philippines, stock prices are affected by interest rate and stock prices in the past. In Singapore, stock prices are affected by the inflation rate.